Spintronic properties of Li1.5Mn0.5Z (Z=As, Sb) compounds in the Cu2Sb structure - Damewood, L.; Fong, C. Y.; Klein, B. M.; Yang, L. H.; Felser, Claudia (Journal of Magnetism and Magnetic Materials, 2015)
We have investigated the spintronic properties of two formula units of Li1.5Mn0.5Z (Z=As, Sb), in the Cu2Sb tetragonal crystal structure based on first-principles density-functional theory calculations, at, and near, their equilibrium (minimum total energy) lattice constants. Two groups of configurations, A and B, are formed for each type of alloy by interchanging Mn with each Li located at four different positions with respect to Li4Z2. Mn has four nearest neighbors in group-A and has one nearest neighbor in group-B. The bonding features of the alloys are compared to the ionic bonding in Li4Z2, and the tetragonal structure of cubic LiMnZ. The magnetic moments of these compounds are reasonably large and range from 3.724 to 4.056 μB, where μB is the Bohr magneton. Both group-B Li3MnZ2, with Z=As, exhibit half-metallic properties at their equilibrium lattice constants while only group-A of the Z=Sb compounds are half-metals. Both the modified Slater-Pauling-Kübler rule and the ionic model can predict the magnetic moments of the alloys showing half-metallicity. The modified rule can be used for exploring other potential half-metals in this class of material.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Ferromagnetic; Half-metals; Spintronic materials